Overexpression of melanoma‐associated antigen D4 is an independent prognostic factor in squamous cell carcinoma of the esophagus. Issue 2 (21st October 2013) - Oya, H.; Kanda, M.; Takami, H.; Hibino, S.; Shimizu, D.; Niwa, Y.; Koike, M.; Nomoto, S.; Yamada, S.; Nishikawa, Y.; Asai, M.; Fujii, T.; et al.
Summary To pursue an urgently needed treatment target for esophageal cancer (EC), we investigated the function of the recently discovered melanoma‐associated antigen (MAGE)‐D4 in squamous cell EC. MAGE‐D4 messenger RNA (mRNA) expression was analyzed in nine EC cell lines using quantitative reverse transcription polymerase chain reaction. In 65 surgical specimens of squamous cell EC with no prior neoadjuvant therapy, MAGE‐D4 mRNA expression in EC tissues and corresponding normal tissues was analyzed and compared, and evaluated in terms of clinicopathological factors. In representative cases, MAGE‐D4 protein distribution was analyzed immunohistochemically. The heterogeneity of MAGE‐D4 mRNA expression was confirmed in EC cell lines by quantitative reverse transcription polymerase chain reaction. In surgical specimens, MAGE‐D4 mRNA expression was significantly higher in EC tissues than in corresponding normal tissues (P < 0.001). Patients with the highest MAGE‐D4 mRNA expression in EC tissues (top quartile, n = 17) had significantly shorter overall survival than patients with low expression (2‐year survival: 44% and 73%, respectively, P = 0.006). Univariate analysis identified age (≥65 years), lymphatic involvement, and high MAGE‐D4 mRNA expression as significant prognostic factors; high MAGE‐D4 mRNA expression was also an independent prognostic factor in multivariable analysis (hazard ratio: 2.194; P = 0.039) and was significantly associated with Brinkman index (P = 0.008) and preoperative carcinoembryonic antigen level (P = 0.002). Immunohistochemical MAGE‐D4b expression was consistent with MAGE‐D4 mRNA profiling. Our results suggest that MAGE‐D4 overexpression influences tumor progression, and MADE‐D4 can be a prognostic marker and a potential molecular target in squamous cell EC.